Jawabanmu

2014-02-16T17:48:12+07:00
1. m =  \frac{y₁ - y₂}{x₁ - x₂}
        =  \frac{-2 - 7}{3 - (-5)}
        =  \frac{-9}{8}
2. 2x + 5y = 11  | x2 = 4x + 10y = 22
    4x - 3y = -17  | x-1=-4x + 3y  = 17
                                 ______________ +
                                          13y = 39
                                              y = 13

   2x + 5y = 11
   2x + 5(13) = 11
   2x + 45 = 11
         2x  = 11 - 45
         2x  = -34
           x  = -17

2x - y = 2(-17) - 13
          = -34 - 13
          = - 47
2014-02-16T17:56:13+07:00
1) x1 = 3 dan y1 = -2
x2 = -5 dan y2 = 7
m = (y1 - y2) / (x1 - x2)
m = (-2 -7) / (3 - (-5))
m = -9/8

2)
2x+5y = 11 |x4| 8x + 20y = 44
4x-3y = -17 |x2| 8x - 6y = -34
                       ____________-
26y = 78
y = 3

2x + 5y = 11
2x + 15 = 11
2x = -4
x = -2

2x - y = 2(-2) - 3 = -4 - 3 = -7

#CMIIW